Which dogs bite?. Issue 1 (March 1991) - Jarrett, P
Abstract : Young children (less than 11 years old) are a particular risk group for dog bites. Dog bites commonly occur from the family pet. Alsatian or alsatian mixes are the biggest group in the study causing dog bites. Alsations are a popular breed. By comparison Retrievers (Labrador and Golden), also a popular breed, caused few bites.